1986
DOI: 10.1007/bf01531713
|View full text |Cite
|
Sign up to set email alerts
|

A validity analysis of selected instruments used to assess autism

Abstract: Differentiating autism from other handicapping conditions, especially mental retardation, has been a constant problem for public schools. This study investigated the effectiveness of three instruments to discriminate autistic from trainable mentally retarded children. The Autism Screening Instrument for Educational Planning, the Childhood Autism Rating Scale, and the Diagnostic Checklist for Behavior Disturbed Children, Form E-2 were administered to 20 autistic and 20 TMR students. Discriminant analysis was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 7 publications
0
32
0
Order By: Relevance
“…Eaves and Milner (1993), who did not have a nonautistic group, found the sensitivity (percentage of correct positives) of the ABC to be 88%. Five studies (Eaves et al, 2000;Sevin et al, 1991;Teal & Wiebe, 1986;Volkmar at al., 1988;Wadden et al, 1991) provided complete classification accuracy statistics. Across all studies, the mean sensitivity was 80%, the mean specificity (percentage of correct negatives) was 86%, and the overall percent of correct classification was 79%.…”
Section: Construct Validitymentioning
confidence: 98%
“…Eaves and Milner (1993), who did not have a nonautistic group, found the sensitivity (percentage of correct positives) of the ABC to be 88%. Five studies (Eaves et al, 2000;Sevin et al, 1991;Teal & Wiebe, 1986;Volkmar at al., 1988;Wadden et al, 1991) provided complete classification accuracy statistics. Across all studies, the mean sensitivity was 80%, the mean specificity (percentage of correct negatives) was 86%, and the overall percent of correct classification was 79%.…”
Section: Construct Validitymentioning
confidence: 98%
“…[13][14][16][17][18][19] The results of such studies, however, vary significantly regarding the sample selection criteria and methodology.…”
Section: -21mentioning
confidence: 99%
“…Other studies have found similar results. Two studies [13][14][15][16][17][18][19][20][21] correctly classified 100% and 85%, respectively, of the children evaluated. However, such results were not obtained in other studies, [14][15][16][17] in which only 50% of the children were correctly classified.…”
Section: -7mentioning
confidence: 99%
See 1 more Smart Citation
“…189 0162-3257/9o/0619o-0189506.0o/0 9 1990 Plenum Publishing Corporation nostic Checklist (1971), the Behavior Rating Instrument for Autistic and Atypical Children (BRIAAC; Ruttenberg, Dratman, Fraknoi, & Wenar, 1966;Ruttenberg, Kalish, Wenar, & Wolf, 1977), the Behavior Observation Scale for autism (BOS;Freeman, Ritvo, Guthrie, Schroth, & Ball, 1978), the Childhood Autism Rating Scale (CARS; Schopler, Reichler, DeVellis & Daly, 1980), the Childhood Autism Behavior Checklist (ABC) of the Autism Screening Instrument for Education Planning (ASIEP; Krug, Arick, & Almond, 1980a, 1980b. More recently, Teal and Wiebe (1986) investigated the effectiveness of three of these scales to discriminate autistic from mentally retarded children: the Rimland's E2, the CARS and the ASIEP. Van Berkelaer-Onnes (1983) reviewed the following autism scales: the Rimland's E2, the BRIAAC, the Diagnostic Rating Scale for Psychotic Children (Reichler & Schopler, 1971), the Checklist for Autistic Children (Makita & Umezu, 1972), and published the Auti-scales for the assessment of very young autistic children.…”
Section: Introductionmentioning
confidence: 99%